KAJIAN TANAMAN JATI (TECTONA GRANDIS) DI DESA SARI NEMBAH KABUPATEN KARO MELALUI ANALISIS KEKERABATAN BERDASARKAN KARAKTER MORFOLOGI - Tarigan, Rio Stefanus; Sipayung, Patricius (AGROSUSTAIN, 2023)
The purpose of this study is to investigate the morphophysiological characteristics of teak plants (Tectona grandis) in Sarinembah Village, Karo Regency. The research method employed in this study is a survey method, focusing on identifying the morphological characteristics of teak plants in Sarinembah Village, Karo Regency, and North Sumatra Province. The study explores the morphological characteristics of teak plants, including leaf color, leaf shape, leaf tip, leaf base, leaf edge, leaf surface texture, leaf vein pattern, height, and diameter of teak trees. The results show variation in leaf color depending on the position on the tree, with leaves typically being elliptical or inverted egg-shaped, pointed at the tip and base with flat edges, rough surface texture, and reticulate leaf veins. Additionally, the height and diameter of teak trees vary, influenced by genetic factors affecting tree growth.